2017
DOI: 10.22159/ajpcr.2017.v10i2.15661
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Prevalence of Anemia and Associated Risk Factors in a Rural Community; A Home-Based Screening

Abstract: Objective: The prevalence of anemia is disproportionately high in developing countries due to poverty, inadequate diet, certain diseases, pregnancy and lactation, and poor access to health services. It is a risk factor for cardiovascular health and early death in adult. To estimate the prevalence of anemia and its associated risk factors in a rural community in India.Methods: Based on inclusion and exclusion criteria, an observational house-to-house survey was conducted for 6 months, by screening for anemia, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The variation in the frequency of the causes of pancytopenia has been attributed to the differences in methodology and stringency of diagnostic criteria, period of observation, varying exposure to myelotoxic agents apart from the geographical area and genetic mutations [19,20]. Screening programs at community level will help in diagnosis and benefit avoiding further complications by offering adequate patient counseling, especially for anemia [21].…”
Section: Discussionmentioning
confidence: 99%
“…The variation in the frequency of the causes of pancytopenia has been attributed to the differences in methodology and stringency of diagnostic criteria, period of observation, varying exposure to myelotoxic agents apart from the geographical area and genetic mutations [19,20]. Screening programs at community level will help in diagnosis and benefit avoiding further complications by offering adequate patient counseling, especially for anemia [21].…”
Section: Discussionmentioning
confidence: 99%
“…Continuous cigarette smoking can have serious negative effects on haematological parameters (including haemoglobin, haematocrit, and red blood cell count) in a healthy population, and these changes can raise the risk of atherosclerosis and cardiovascular diseases [ 23 ]. In that regard, a number of studies have shown that the levels of Haemoglobin are low in smokers [ 24 , 25 ]. That notwithstanding, evidence suggests a protective role of cigarette smoking against anaemia due to erythropoietin-stimulating influence of smoking-induced increase in carbon monoxide [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%